Clinical and survival of retinoblastoma patients treated at the National Institute of Neoplastic Diseases January 2001 - august 2007 - Blanco, William Milton Rodrigo (2013)
Objectives: To describe the clinical features and survival of patients with retinoblastoma treated at the National Institute of Neoplastic Diseases (INEN) over a period of 07 years. The information included gender, laterality, and diagnosis age, presenting signs, place of origin, reference medical center and survival rate. Methods: Descriptive, observational, retrospective and cross-sectional study was carried out. We reviewed 220 patients with retinoblastoma treated at the INEN Results: The average age was 2.4 years. Of these (75 %) had unilateral presentation and (25 %) bilateral; six cases had family history. The most common presenting signs were leukokoria (56.36%), amaurosis (10.45%) and proptosis (9.55%). 91 patients were from Lima, 129 from provinces. The patients were classified according to the TNM (Tumour, Node and Metastesis) classification in stage I: 5 patients, stage II: 93 patients, stage III: 65 patients, stage IV: 57 patients. The 5 year survival for stage I was 100% in stage II (98.8%) in stage III (81.9%) and stage IV (7.8%). Care centers who reported the most cases of retinoblastoma were: National Eye Institute, Private Centers and the National Institute of Child Health. Conclusions: The clinical data and clinical stage distribution of this series were similar to previous studies conducted at the INEN, but there was an increase in survival in stage II and III.